Urgensi Pengembangan Regulasi Emosi dalam Mendukung Children Well-Being pada Anak Usia Dini - Najwa Salsabila; Taopik Rahman; Risbon Sianturi (Sekolah Tinggi Agama Islam Al-Kifayah Riau, 2026)
This study aims to examine the urgency of developing emotional regulation in supporting children’s well-being in early childhood. Emotional regulation is one of the important aspects of social-emotional development that needs to be fostered from an early age, as it influences children's ability to recognize, manage, and express emotions appropriately. Children’s well-being refers to a condition in which children feel safe, comfortable, happy, valued, and able to establish positive social relationships in their daily lives. This study employs a literature review method by analyzing various relevant scientific references, including journals, books, and previous research findings. The results indicate that the development of emotional regulation plays a significant role in supporting children’s well-being, particularly in enhancing children’s emotional stability, self-confidence, social adjustment, and positive interactions with others. Therefore, emotional regulation development needs to be optimized through the role of parents, teachers, and a supportive environment in order to create holistic well-being in early childhood